On the patterns of behaviour in digitalized societies - Horst Hanusch (Universität Augsburg, Institut für Volkswirtschaftslehre, 2016)
The study intends (1) to look at the importance of individual rationality as the main principle of economic behaviour, incorporated best in the concept of "homo oeconomicus". (2) to show how the third technological revolution, the "digitalization of society", may transform individual behaviour in the three pillars of an economic system (real, financial, public). One major achievement of main stream economics of Western style is the "homo oeconomicus". Behind this concept stands the idea of rational man relevant for all parts in economic systems. It allows a consequent application of profit and efficiency maximizing in the real and financial sector and of vote and utility maximization in the public sector as agents' behaviour. Psychology, sociology, behaviourism, anthropology are strictly against the idea of the "homo oeconomicus". Evolutionary and Neo-Schumpeterian Economics also claim that it is wrong because it doesn't allow to include uncertainty considerations which are a condition sine-qua-non for innovation, change and prosperity. But, is this concept completely wrong? Or is it perhaps relevant for specific parts of an economic system, if they develop within the process of digital revolution? These are the questions which will be tackled in the paper. The analysis will follow a comprehensive approach, looking at the three institutional pillars of an economy, the financial, the real and the public sector trying to work out the effects of digitalization on the patterns of behaviour. All in all, the effects of digitalization can be summarized as follows: In the financial pillar it modifies the culture of doing business from "symbiotic capitalism" to "financial capitalism" with prevailing olympic rationality. In the industrial pillar it induces changes from short term maximizing "managerial capitalism" to a long term oriented "entrepreneurial capitalism". In the public pillar it may open ways to institutional change, at least partially, from a "bureaucratic tax state" to a system of "social capitalism" with high potentials for enabling individual creativity and resilience capabilities.
urn:nbn:de:bvb:384-opus4-710777
Keywords: B52; D00; O1; 330; Behavioural Economics; Neo-Schumpeterianism